A systematic review of research on sitting and working furniture ergonomic from 2012 to 2022: analysis of assessment approaches - Bai, Yifan; Kamarudin, Khairul Manami; Alli, Hassan (Elsevier, 2024)
This study analyses which aspects of sitting and working furniture ergonomics that may be influenced and how they are assessed. To gather information on the types and assessment techniques connected with influencing furniture ergonomics, a systematic review of the literature was conducted. The papers in the systematic review were published between 2012 and 2022. The articles applied the Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines to limit the 41 papers that were eventually included (N = 41) to those containing keywords like ergonomics, human factors, comfort, working furniture, Chair, assessment and evaluation. The research objective of this systematic review is to provide a comprehensive overview of sitting and working furniture and the main findings, obtaining common assessment techniques for this type of furniture and their suitability. According to the relevant studies, the publications were categorized by summarizing factors like region, gender, research methods, ergonomic assessment techniques and methods used, correlation between assessment techniques and methods, etc. Summaries of the data extracted from the included papers are provided and the applicability of some approaches are assessed. Only a small number of authors have evaluated the ergonomics of furniture used in homes. One of the research gaps is the paucity of research on gender segregation, secular trends, and cultural contexts. These studies heavily rely on quantitative research techniques, and the articles may lack credibility due to the homogeneity of the evaluation techniques. Finally, the authors offer some suggestions for the appropriate ergonomic analysis of furniture.